Penerapan Customer Relationship Management Untuk Menjaga Loyalitas Pelanggan Waroeng Steak and Shake (WSS) di Kota Malang. - Choirun nisa; Djumilah Zain (Jurnal Ilmiah Mahasiswa FEB, 2014)
This  study  aims  to  find  the  influence  of  customer  orientation,  customer relationship  management  (crm)  organization,  knowledge  management,  to customer royalty Waroeng Steak and Shake (WSS) in Malang. Sampling technique that  use  in  this  study  was  purposive  sampling  and  obtained  a  sample  of  100 respondents  who  are  customers  of  Waroeng  Steak  and  Shake  (WSS).  Data analysis was perfomed by using  the  classical assumption and hypothesis  testing using multiple linear regression analysis. The  results of  this  study  indicate  that customer  relationship variable and knowledge management are not significantly influence to customer loyalty. While the  customer  relationship  management  organization  is  the  only  variable  that significantly the customer loyalty.